Analysis of Air Pollution (SO2) at Some Point of Congestion in DKI Jakarta - Kurnia Aji Tritamtama; Fred Erick Soaloan Sembiring; Achmad Choiruddin; Harry Patria (Disease Prevention and Public Health Journal, 2023)
Background: Air pollution is the entry or inclusion of energy substances from other components into the air by humans so that air quality drops to a certain level which causes the air to not meet the requirements. This study aims to determine concentration levels of particulates (PM10, PM25), sulfur dioxide (SO2), carbon monoxide (CO), ozone (O3), and nitrogen dioxide (NO2) at several congestion points in Daerah Khusus Ibukota (DKI) Jakarta. Method: The research location based on the purposive sampling method was carried out at 5 congestion points in DKI Jakarta namely Bundaran Hotel Indonesia (HI), Kelapa Gading, Jagakarsa, Lubang Buaya, and Kebon Jeruk. The data used in the process of forming the model using the Box-Jenkins method and analyzed manually, so this process can be done using ARIMA Forecasting. Results: Based on the time series of hourly data, which was calculated on average into daily data, the concentration of PM10, PM25, SO2, CO, O3, and NO2 from January to October 2021 has decreased from the previous months at several congestion points in DKI. Conclusion: The conclusion of this study is the decreased concentration of PM10, PM25, SO2, CO, O3, and NO2 at several points in DKI Jakarta, so it is recommended to the Government and the Community make efforts/activities to maintain the healthy air quality in DKI Jakarta.